2004
DOI: 10.1023/b:bebm.0000035136.61014.c2
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Biological Activity of Lipopolysaccharide in the Complex with Chitosan

Abstract: In the complex with chitosan, lipopolysaccharide partially lost its ability to induce lymphokines tumor necrosis factor and interleukin-8, but retained immunostimulating properties and increased phagocytic function of macrophages by improving digestion of bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Since chitosan is a chitin derivative, there is the possibility of endotoxin presence, which could result in inflammation [13]. There is information on the anti-inflammatory effect of the complex of chitosan and lipopolysaccharide, which is the most common endotoxin, [14] as well as about its partial dissociation [15] on interaction with chitosan. Moreover, the treatment of endotoxins with acids and alkalis (more than 0.1 M) results in partial destruction [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since chitosan is a chitin derivative, there is the possibility of endotoxin presence, which could result in inflammation [13]. There is information on the anti-inflammatory effect of the complex of chitosan and lipopolysaccharide, which is the most common endotoxin, [14] as well as about its partial dissociation [15] on interaction with chitosan. Moreover, the treatment of endotoxins with acids and alkalis (more than 0.1 M) results in partial destruction [16].…”
Section: Introductionmentioning
confidence: 99%
“…Such cationic compounds as lysozyme [8] and polymyxin [7] neutralize endotoxins by forming macromolecular complexes with them. We previously showed that chitosan, a natural polysaccharide, forms stable complexes with endotoxins, thus appreciably reducing their toxicity [1] and modifying biological properties of LPS [2]. Here we studied the possibility of using polysaccharide carrageenan for this purpose.…”
mentioning
confidence: 99%
“…Second, the complex reaction of LPS and CMC may reduce the inflammatory response. In fact, a previous study showed that LPS has an anion and CMC has a cation; thus, when the two substances react, they form a complex (5,7). This suggests that the inflammatory response to LPS is reduced, and therefore, the reaction to chitosan cannot be clearly observed.…”
Section: Wwwksvcorkrmentioning
confidence: 96%
“…To the best of our knowledge, the effects of CMC on the proliferation and migration of canine BMSCs in vitro have been reported here for the first time. LPSs are a major component of cell walls in gram-negative bacteria; they modulate the activities of most systems in infected microorganisms, inducing various pathophysiological changes (7). The molecules of LPS exhibit a variety of biological activities that may be beneficial at low concentrations but may be endotoxic at higher concentrations due to an overproduction of cytokines by immune cells, such as TNF-α and ILs (5).…”
Section: Wwwksvcorkrmentioning
confidence: 99%